Role of Hematopoietic Stem Cell Transplantation in Acute Promyelocytic Leukemia - Sanz, Jaime; Montesinos, Pau; Sanz, Miguel A. (Frontiers in Oncology, 2021)
The indication of hematopoietic stem cell transplantation (HSCT) in acute promyelocytic leukemia (APL) has evolved historically from a widespread use in front-line therapy during the pre-ATRA era to a virtual rejection of this indication for patients treated with modern treatments. HSCT in first complete remission could only be considered for an extremely small fraction of patients with persistent MRD at the end of consolidation or for those who relapse. In the pre-ATO era, relapsed patients were usually treated with readministration of ATRA and chemotherapy as salvage therapy, generally containing high-dose cytarabine and an anthracycline, followed by further post-remission chemotherapy and/or HSCT. ATO-based regimens are presently regarded as the first option for relapsed APL. The selection of the most appropriate post-remission treatment option for patients in second CR (CR2), as well as the modality of HSCT when indicated, depends on several variables, such as pre-transplant molecular status, duration of first remission, age, and donor availability. Although with a moderate level of evidence, based on recent retrospective studies, autologous HSCT would be at present the preferred option for consolidation for patients in molecular CR2. Allogeneic HSCT could be considered in patients with a very early relapse or those beyond CR2. Nevertheless, the superiority of HSCT as consolidation over other alternatives without transplantation has recently been questioned in some studies, which justify a prospective controlled study to resolve this still controversial issue.